Stent graft placement for an incidental finding of hepatic artery pseudoaneurysm post hepatectomy, a case report and literature review. (2018) - Aoun, Charbel; El Rassi, Ziad
Highlights: Hepatic artery pseudoaneurysm presentation, diagnosis, and treatment options. Stent graft placement post hepatic artery pseudoaneurysm is safe and effective. General and vascular surgeons should be on the case to manage any complication. Abstract: Introduction: Hepatic artery pseudoaneurysm is usually iatrogenic, with bleeding occurring early or late postoperatively. Case presentation: A 61-year-old man with pseudoaneurysm of the common hepatic artery post hepatectomy treated with a stent-graft. The patient was asymptomatic and the pseudoaneurysm appeared incidentally on follow-up. Selective catheterization of the common hepatic artery showed a pseudo-aneurysm close to its origin. Covered stent was deployed in the main hepatic artery. Completion angiography showed no residual spasm and adequate patency of the common hepatic artery, with complete exclusion of the pseudoaneurysm. Discussion: Using stentgraft for pseudoaneurysm management has multiple advantages when compared to other traditional techniques. However, stent placement has its own complications. Conclusion: Stent graft placement post hepatic artery pseudo-aneurysm is safe and effective; however its complications should be evaluated with multidisciplinary team.